2016
DOI: 10.1515/jpm-2015-0387
|View full text |Cite
|
Sign up to set email alerts
|

Is there a sex difference in fetal behavior? A comparison of the KANET test between male and female fetuses

Abstract: Our results show that there is no difference in fetal behavior between male and female fetuses in the third trimester of pregnancy. These results suggest that 4D ultrasound study examining fetal behavior does not need to consider the factor of fetal sex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…In line with most previous research (Conde et al, ; de Vries et al, ; Hata et al, ; Mulder et al, ; Reissland et al, ), no differences were found between males and females in mean levels and trajectories of breathing movements. However, sex differences were found for general movements, such that male were more active than female fetuses at 21 weeks of gestation and males had a steeper decline in general movements incidence during the second half of pregnancy.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In line with most previous research (Conde et al, ; de Vries et al, ; Hata et al, ; Mulder et al, ; Reissland et al, ), no differences were found between males and females in mean levels and trajectories of breathing movements. However, sex differences were found for general movements, such that male were more active than female fetuses at 21 weeks of gestation and males had a steeper decline in general movements incidence during the second half of pregnancy.…”
Section: Discussionsupporting
confidence: 91%
“…Fetal movements appear to be associated with a number of factors including fetal sex, gestational age at birth, and birth weight. Regarding fetal sex, the results are inconsistent, with some studies showing that male fetuses are more active than female fetuses (Almli, Ball, & Wheeler, ; DiPietro, Hodgson, Costigan, Hilton, & Johnson, ), while most studies failed to find any sex differences in fetal movements incidence (Conde et al, ; de Vries, Visser, & Prechtl, ; Hata et al, ; Mulder et al, ; Reissland, Francis, Aydin, Mason, & Exley, ; Robles de Medina, Visser, Huizink, Buitelaar, & Mulder, ). The absence of breathing movements has been identified as the best predictor of preterm birth (Boots et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…There was no difference in KANET scores between male and female fetuses in the third trimester of pregnancy. 35 When evaluating the effect of parity on fetal behavior between primi-and multiparas, there was no significant difference in the total KANET score between the two groups. 36 However, a significant difference in just one fetal movement, isolated eye blinking, between the groups was found.…”
Section: Kurjak's Antenatal Neurodevelopmental Testmentioning
confidence: 88%
“…This study suggests that ethnicity should be considered when evaluating fetal behavior, especially during the assessment of fetal facial expressions. There was no difference in KANET scores between male and female fetuses in the third trimester of pregnancy . When evaluating the effect of parity on fetal behavior between primi‐ and multiparas, there was no significant difference in the total KANET score between the two groups .…”
Section: Kurjak's Antenatal Neurodevelopmental Testmentioning
confidence: 92%
“…3 The scoring system is as follows: 0-5 is abnormal, 6-9 is borderline, and 10-16 is normal. [4][5][6][7] However, it must be remembered that the modified KANET assessment still involves a learning curve, and it may be unfamiliar to beginners. Furthermore, this test necessitates high-level operator-dependent 4D reconstruction of fetal behaviors.…”
Section: Introductionmentioning
confidence: 99%